A Study of the Relationship between Family Communication Patterns and Adolescents’ Pre-Purchase Decision-Making Process - Shahriar Azizi; Abasali Haji Karimi; Saedeh Haji Ebrahimi; Amin Dini (جامعه شناسی کاربردی, 2013)
Introduction Today's adolescents have a great influence on the family purchasing behavior. Adolescent's critical role is based on the four pillars: 1) they have more money for purchasing, 2) they are potential consumers in the future, 3) adolescents influence family purchasing decisions (Hawkins, 2006), and 4) they receive more attention from their parents. According to the last statistics of IRAN general census in 2006, adolescents (aged 15-19) composed %38.12 .of the total population. So understanding the purchasing behavior of this population category is very critical to marketing managers. On the other hand, family communication patterns impact adolescents' attitudes and behavior. Based on investigation of the current literature, it is clear that in the three-step consumer behavior process, that is, pre-purchase, purchase and post-purchase, the first step has not been studied adequately before. In this research, we try to study the impact of family communication patterns on the adolescent's pre-purchase decision-making process. McLeod & Chafee (1972) provided a typology for parent-child communication schema. Their typology based on two types of parent-child communication: socially oriented which care about complying social norms and concept oriented which concerns persuading the children to convey their viewpoints and attitudes freely regardless of the norms. In 1981, Moore and Moschis categorized parent-child communication patterns, based on McLeod & Chafee's typology, to four different pattern types. Their four-dimensional typology has two axes from high to low. The first axis is socially oriented communication and the second is concept oriented communication. So we have a 2*2 cells matrix. Low concept with social orientation shows a laissez faire pattern. Low concept orientation with high social orientation shows a protective schema. In low social orientation with high concept orientation, a pluralistic pattern emerges. If social and concept orientations are high simultaneously, a consensual schema emerges. According to the literature review we formulate 12 hypotheses as below: H1: Adolescents' proactive problem recognition is higher in families with high concept orientation than families with lower concept orientation. H2: Adolescents' in families with high concept orientation use internal source of information more than families with lower concept orientation. H3: Adolescents' in families with high concept orientation use their parents as source of information more than families with lower concept orientation. H4: Adolescents' in families with high concept orientation use their friends and classmates as sources of information more than families with lower concept orientation. H5: Adolescents' in families with high concept orientation use business advertisements as source of information more than families with lower concept orientation. H6: volume of the external search of adolescents' in families with high concept orientation is greater than families with lower concept orientation. H7: Adolescents' in families with high concept orientation trust more to business advertisements than families with lower concept orientation. H8: Adolescents' in families with protective communication pattern pay attention to their parents preferences while evaluate options. H9: Adolescents' in families with protective communication pattern pay attention to their friends and classmates preferences while evaluate options. H10: Adolescents' in families with pluralistic communication pattern pay attention to product brand while evaluate options. H11: Adolescents' in families with consensual communication pattern pay attention to product price while evaluate options. H12: Adolescents' in families with protective communication pattern pay attention to product quality while evaluate options.